Bacillus subtilis Produces Amino Acids to Stimulate Protein Synthesis in Ruminal Tissue Explants via the Phosphatidylinositol-4,5-Bisphosphate 3-Kinase Catalytic Subunit Beta–Serine/Threonine Kinase–Mammalian Target of Rapamycin Complex 1 Pathway - Wang, Qiuju; Ren, Yulong; Cui, Yizhe; Gao, Bingnan; Zhang, Hao; Jiang, Qianming; Loor, Juan J.; Deng, Zhaoju; Xu, Chuang (Frontiers in Veterinary Science, 2022)
Background: Bacillus subtilis is a probiotic strain with demonstrated benefits as a feed supplement in ruminants. In this study, one Bacillus subtilis strain isolated from ruminal fluid of Holstein dairy cows was used for an ex vivo study with ruminal tissue explants. The main goal was to assess potential endosymbiotic links between Bacillus subtilis and ruminal epithelium using molecular analyses and amino acid profiling. The explant culture protocol was first optimized to determine ideal conditions in terms of tissue viability before performing the actual experiments involving active or inactive bacteria with or without protein synthesis inhibitors. Results: PIK3CB, AKT, MTOR, P70S6K1, and 4EBP1 mRNA abundance was highest (P<0.01) and PDCD4 was the lowest when tissue was incubated with 107 of Bacillus subtilis. Compared with inactivated bacteria, expression of PIK3CB，AKT，and overall changes in MTOR and P70S6K1 were greater in rumen explants with live bacteria (P<0.05).The expression trend of protein and gene expression was consistent in the bacterial concentration. There were differences in the concentrations of individual amino acids in the supernatant of live and inactivated bacteria culture groups, with most amino acids enriched in pathways such as aminoacyl tRNA biosynthesis, cyanoamino acid metabolism, monobactam biosynthesis, or glycine, serine, and threonine metabolism. Addition of the chemical compound psilocybin upregulated expression of PIK3CB and AKT. A significant decrease (P<0.05) of PIK3CB and mTOR protein expression was detected after adding LY294002 and Rapamycin. In addition, those responses were associated with downregulation (P<0.05) of AKT and P70S6K protein expression. Conclusions: We confirmed that amino acids produced by Bacillus subtilis can promote protein synthesis in ruminal tissue explants by altering the expression of related factors in the PIK3CB-AKT-mTORC1 pathway. The ex vivo ruminal tissue culture system provides a suitable model for studying probiotic-induced alterations in tissue function. As such, it provides the means for future mechanistic studies related to microbial regulation and the dietary supply of protein. In the long-term, such studies could aid in optimizing feed efficiency and reducing feeding costs in dairy cow farming.